2021
DOI: 10.3390/ijerph182412890
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Indoor Particulate Matter on Blood Indicators Related to Anemia

Abstract: Exposure to indoor particulate matter (PM) is a potential risk factor that increases systemic inflammation and affects erythropoiesis. This study investigated the association between exposure to indoor PM and blood indicators related to anemia (BIRA) in housewives. Indoor PM and blood folate status are important factors in the risk of anemia. This was a housewife cohort study; we recruited 284 housewives in Seoul and Ulsan, Republic of Korea. Indoor exposure to PM2.5 and PM10 was measured by gravimetric analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Trenton et al suggested that NO 2 and PM 2.5 were signi cantly associated with an increased prevalence of anemia and reduced Hb levels in older Americans, that there were dose-response relationship, and that acute response protein signi cantly mediates this effect of PM 2.5 (Honda et al 2017). Consistent with our study, a cross-sectional study of Korean housewives showed that while the overall effect of PM 2.5 exposure was a decrease in mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCH), PM 2.5 was also signi cantly negatively correlated with serum folate levels (Kwag et al 2021). A recent survey of rural Chinese women also supports the idea that long-term use of solid fuels such as coal or wood may lead to insu cient red blood cell folate levels (Xia et al 2023).…”
Section: Discussionsupporting
confidence: 89%
“…Trenton et al suggested that NO 2 and PM 2.5 were signi cantly associated with an increased prevalence of anemia and reduced Hb levels in older Americans, that there were dose-response relationship, and that acute response protein signi cantly mediates this effect of PM 2.5 (Honda et al 2017). Consistent with our study, a cross-sectional study of Korean housewives showed that while the overall effect of PM 2.5 exposure was a decrease in mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCH), PM 2.5 was also signi cantly negatively correlated with serum folate levels (Kwag et al 2021). A recent survey of rural Chinese women also supports the idea that long-term use of solid fuels such as coal or wood may lead to insu cient red blood cell folate levels (Xia et al 2023).…”
Section: Discussionsupporting
confidence: 89%
“…Another study conducted in Chinese cities, using both panel and cross-sectional designs, found that PM 2.5 had a positive association with PLT but a negative association with RBC [13]. Researchers in the Korean Children's Environmental Health Study observed a negative correlation between indoor PM 2.5 and HGB and HCT levels [14]. Furthermore, a recent investigation in Beijing reported that elevated PM 2.5 levels were associated with a decrease in PLT [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have examined the impact of PM 2.5 on erythrocyte and platelet parameters, including RBC, HGB, HCT, and PLT. Nevertheless, the findings from these studies have been inconsistent and even contradictory [13][14][15][16]. These discrepancies may be attributed to differences in study design, population characteristics, and methods used for exposure assessment [13,17].…”
Section: Introductionmentioning
confidence: 99%
“…So, to prevent anemia in these housewives’ folate intake shall be recommended along with the least exposure to PMs. [ 163 ]…”
Section: Association Of Particulate Matters With Various Disordersmentioning
confidence: 99%